ONE BONE FOREARM: A VALID OPTION FOR TREATING POST INFECTION BONE DEFICIENCIES - Zamir, Mehroze; Taufiq, Intikhab; Farooq, Mohammad Zoha (Journal of Ayub Medical College Abbottabad, 2019)
Surgical fixation of radius to ulna has been described in the literature at various instances when deficiencies of either of the bones are encountered. The main concept of one bone forearm relies on an intact elbow and wrist articulations so a stable functioning limb can be achieved after union of radius to the ulna. This case report elaborates post infection loss of proximal ulna treated with fixation to radius. Keywords: Forearm/surgery; Radius/abnormalities; Ulna/abnormalities; Osteomyelitis; Complications